Spectral Fidelity - AAVV (Il Colle di Galileo, 2024)
This is a very exciting time for the spectroscopic community. So much exquisite data are available in several fields, such as exoplanets, stars, galaxies and quasars, thanks to high-resolution, high-precision and accuracy spectrographs. It is time to discuss spectral fidelity and what we can expect from the future.